2015
DOI: 10.1002/pro.2765
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH modulates quinary structure

Abstract: NMR spectroscopy can provide information about proteins in living cells. pH is an important characteristic of the intracellular environment because it modulates key protein properties such as net charge and stability. Here, we show that pH modulates quinary interactions, the weak, ubiquitous interactions between proteins and other cellular macromolecules. We use the K10H variant of the B domain of protein G (GB1, 6.2 kDa) as a pH reporter in Escherichia coli cells. By controlling the intracellular pH, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 65 publications
1
77
0
Order By: Relevance
“…During the same time, the term ‘quinary structure’ (the fifth level of protein structural organization) was coined by McConkey (McConkey, 1982) to describe transient protein-protein interactions. These interactions are not only low in thermodynamic stability (K D  > 1 μM), but also have a low kinetic barrier (Wirth and Gruebele, 2013), thereby making them amenable to modulation by cellular variations like metabolite concentrations, pH (Cohen et al, 2015; Cohen and Pielak, 2016), crowding, etc. Till date, the multi-enzyme complex metabolon remains to be the best example of a quinary structure.…”
Section: Discussionmentioning
confidence: 99%
“…During the same time, the term ‘quinary structure’ (the fifth level of protein structural organization) was coined by McConkey (McConkey, 1982) to describe transient protein-protein interactions. These interactions are not only low in thermodynamic stability (K D  > 1 μM), but also have a low kinetic barrier (Wirth and Gruebele, 2013), thereby making them amenable to modulation by cellular variations like metabolite concentrations, pH (Cohen et al, 2015; Cohen and Pielak, 2016), crowding, etc. Till date, the multi-enzyme complex metabolon remains to be the best example of a quinary structure.…”
Section: Discussionmentioning
confidence: 99%
“…The quinary interaction of trans -type has been demonstrated to stabilize protein structure in crowded solutions, i.e. , in cells, using H-D exchange NMR [38,39]. Here the cis -type of quinary structure attributes has been derived from dilution-injection-SEC-FPLC curves (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the role of charge‐charge interactions in quinary structure, we quantified GB1 stability in E. coli cells at different pH values. Using the K10H variant of GB1 to report on intracellular pH and a buffer to control the intracellular pH, we showed that the quality of the in‐cell HSQC spectrum degrades at lower pH values . We used the quenched lysate method to quantify GB1 stability at different pH values to show that lowering the pH destabilizes the protein to a greater extent in cells than in buffer .…”
Section: Characterizing Quinary Structurementioning
confidence: 99%